Penggunaan Media Flashcard dalam Pembelajaran Mufrodat (Kosa Kata Bahasa Arab) Pada Anak Usia Dini Taman Kanak-Kanak (TK) Al-Ihsan - Meydani Saputri; Harahap, Eliva Azzahra (Jurnal Al-Hibru, 2026)
The observed problem is the lack of appropriate media use in vocabulary learning. Therefore, this study aims to provide innovation to educational institutions so that they can consider flashcard media as a medium used in vocabulary learning. This media can be used continuously, so that the Arabic vocabulary that children learn is not only temporary material, but becomes a provision for children's language skills. This study used a qualitative approach with data collection techniques in the form of interviews, observations, and documentation to obtain information related to Arabic language learning and became an active participant to determine children's abilities after using flashcard media. The results show that flashcard media is a suitable medium for use in Arabic language learning, especially vocabulary for early childhood. This is proven because flashcard media can make it easier for children to memorize vocabulary, understand Arabic writing, train focus, and be interactive in learning. Thus, teachers are expected to continue to use flashcard media creatively and in a variety of ways as a medium for Arabic language learning for early childhood.